The lost executioner : a journey to the heart of the killing fields - Dunlop, Nic, author 1969- (New York : Walker & Company, 2006)
In Cambodia, between 1975 and 1979, two million people died at the hands of the Khmer Rouge. Twenty years later, not one member had been held accountable for the genocide. Haunted by the image of one of them, Comrade Duch, photographer Nic Dunlop set out to bring him to life, and thereby to account. "I needed to understand how a seemingly ordinary man ... could turn into one of the worst mass murderers of the twentieth century." Dunlop unfolds the history of Cambodia as a filter for understanding its tragic last forty years. Guided by witnesses, he teases out the details of Duch's transformation from sensitive schoolchild and dedicated teacher to the revolutionary killer who later slipped quietly back into village life. This result is a vivid reminder that, whether in the killing fields of Cambodia or the deserts of Darfur, if we turn our backs on genocide, we must bear a collective guilt.--From publisher description
"First published in the United Kingdom in 2005 by Bloomsbury Publishing"--T.p. verso
Includes bibliographical references (p. [318]-324)
Keywords: Kang, Kech Ieu; Parti communiste du Kampuchea; Cambodia -- History -- 1975-1979